2016
DOI: 10.1002/dc.23524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of RNA and DNA extraction from liquid‐based cytology specimens

Abstract: Molecular diagnosis using DNA and RNA derived from malignant tumors and molecular biological tools such as the quantitative polymerase-chain-reaction (qPCR) is a commonly used technique in clinical pathology. In this report, we compared the qualitative extraction of RNA and DNA from cancer cells fixed using several liquid-based cytology (LBC) kits. Ten to 1,000 cells from the T24 urinary bladder cancer cell line and SKG-II cervical cancer cell line were fixed with 55% methanol and three different methanol-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Cytologic samples provide high‐quality DNA for molecular testing and are comparable, or even superior to, formalin‐fixed, paraffin‐embedded surgical pathology specimens for the evaluation of clinically relevant mutations . Liquid‐based cytology (LBC) makes it possible to perform additional techniques, such as immunocytochemistry and in situ hybridization, and also allows for molecular testing using DNA and RNA extracted from the remaining fixed cells . Some studies have demonstrated that LBC systems provide excellent cell preservation for routine cytopathology and can be used for DNA‐ and RNA‐based molecular testing …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytologic samples provide high‐quality DNA for molecular testing and are comparable, or even superior to, formalin‐fixed, paraffin‐embedded surgical pathology specimens for the evaluation of clinically relevant mutations . Liquid‐based cytology (LBC) makes it possible to perform additional techniques, such as immunocytochemistry and in situ hybridization, and also allows for molecular testing using DNA and RNA extracted from the remaining fixed cells . Some studies have demonstrated that LBC systems provide excellent cell preservation for routine cytopathology and can be used for DNA‐ and RNA‐based molecular testing …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Liquid-based cytology (LBC) makes it possible to perform additional techniques, such as immunocytochemistry and in situ hybridization, and also allows for molecular testing using DNA and RNA extracted from the remaining fixed cells. [4][5][6] Some studies have demonstrated that LBC systems provide excellent cell preservation for routine cytopathology and can be used for DNA-and RNAbased molecular testing. 4,5 The 2015 World Health Organization classification 7 classifications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, shipping and storage of frozen RNA is expensive, requires special handling and Ultra-Low-Temperature freezers, and is time sensitive. The extraction of DNA and RNA from liquid-based cytology specimens has previously been studied [6,7].…”
Section: Main Textmentioning
confidence: 99%
“…Some commercial preservative solutions for LBC include formaldehyde to improve the imaging of specimens; however, the percentage of formaldehyde in LBC preservation solutions usually is lower than that in common fixative solutions such as buffered formalin for FFPE specimens. Recently, Fujii et al reported that genomic DNA extracted from human urothelial carcinoma and cervical cancer cell lines that were fixed in several commercial LBC solutions could be used in genetic analyses, although DNA expression decreased with longer fixation times.…”
Section: Introductionmentioning
confidence: 99%